Induced response of soil properties and Oribatid mites (Acari, Cryptostigmata) community structure after the conversion of tropical secondary forests into oil palm and rubber plantations - Kouadio Julien, Julien; KOFFI, Raymond Yao Ray; MANOU, Saint Cyrille Kouamé; DIARRA, Basile Moustapha; TOSSA, Paulin N’Da Ezin; ADY, Randolphe Jean Kouassi (JOURNAL OF ADVANCES IN AGRICULTURE, 2022)
The aim of investigation was to address the impacts of tropical forests conversion into agricultural land on changes in Oribatid mites’ communities as well as soil physico-chemical properties across 2–4 texturally distinct soils in La Mé and Grand Lahou, Côte d’Ivoire. The fieldwork was conducted in the humid period on two study sites: 1– rubber landscape (secondary forest, 7-, 12- and 25-year-old rubber plantations) and 2– oil palm landscape (secondary forest, 13-, 20- and 39-year-old oil palm plantations). Three sampling areas were established on each land-use type and age class, for a total of 24 sampling areas. In each sampling area, soil cores for Oribatid mite’s extraction were taken at a depth of 10 cm across a 40–50 m transect. The soil physical and chemical properties were also measured. The results showed a decrease in Oribatid density (–29% and –71%), species richness (–29% and –42%), diversity (–29% and –59%), soil organic carbon (–56% and –17%), total nitrogen (–55% and –12%) and soil organic matter (–56% and –17%), and an increase in bulk density (+28% and +21%), respectively after the conversion of the secondary forests into rubber and oil palm plantations. Whatever the study site, the soil physico-chemical and biological properties were more stabilized in the clay and clay sandy textures compared to sandy clay and sandy soil textures. Our findings suggest the incorporation of woody trees with an understory of nitrogen-fixing legume species as a cover crop, which can create a sustainable agroforestry system with improved land quality.